2020
DOI: 10.7556/jaoa.2020.145
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Social Support and Diabetes-Related Distress in People With Type 2 Diabetes Mellitus

Abstract: Context Diabetes is a complex, chronic condition and managing it can have psychosocial implications for patients, including an impact on relationships with their loved ones and physical wellness. The necessary modifications to daily behaviors can be very overwhelming, thus leading to diabetes-related distress. Objective To investigate the association between diabetes-related distress and perceived social support among people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…While self-management of T2D is rooted in the individual, studies have shown that family members play crucial supportive roles in managing diabetes of a loved one (Thirsk & Schick-Makaroff, 2021 ). Increased familial support has been shown to decrease diabetes-related distress (Young, et al, 2020 ). Thirsk and Schick-Makaroff ( 2021 ) have found that framing of a health issue, whether it be individual or familial, can impact chronic disease management and the provision of family support.…”
Section: Discussionmentioning
confidence: 99%
“…While self-management of T2D is rooted in the individual, studies have shown that family members play crucial supportive roles in managing diabetes of a loved one (Thirsk & Schick-Makaroff, 2021 ). Increased familial support has been shown to decrease diabetes-related distress (Young, et al, 2020 ). Thirsk and Schick-Makaroff ( 2021 ) have found that framing of a health issue, whether it be individual or familial, can impact chronic disease management and the provision of family support.…”
Section: Discussionmentioning
confidence: 99%
“…The accompaniment of professional medical personnel and of the other group members might have led to greater subjectively perceived social support. Young et al [ 27 ] assert that diabetes-related stress is lower when greater subjective social support is perceived. The fact that the participants prepared for the hiking tour may be another reason why the PAID scores were relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on 101 patients with T2DM demonstrated that higher perceived support from family members was significantly associated with lower total DRD scores. 36 On the other hand, recent data also showed that not only patients with diabetes are affected by psychological conditions, but also family members (spouses) whom are at higher risk of developing depression/anxiety. The risk is driven by the severity of patient's diabetes.…”
Section: Discussionmentioning
confidence: 99%